Marketing Innovation for Mandar Brown Sugar Products Through E-Commerce in the Tunas Sejahtera Business Group in Padang Village, Polewali Mandar Regency - Kartika, Eka Dewi; Laitupa, Salma (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Sales of Mandar brown sugar were carried out by the Tunas Sejahtera business group in Padang Village, Campalagian District. At the initial observation, the Tunas Sejahtera business group consisted of 10 housewives and 5 young people from Padang Village. The Mandar brown sugar products produced are marketed or sold in traditional markets in the Campalagian, Wono and surrounding areas, as well as shops and kiosks in the Campalagian, Wono and Padang Village areas. The distribution of Mandar brown sugar products is very limited and is not well known to consumers, so that Mandar brown sugar production cannot be produced in large quantities due to limited marketing or sales capabilities due to marketing reach being very limited to certain areas.